Proposal on integrated fire alarm system for I.T.M / Rosly Deraman. - Deraman, Rosly (1988)
A fire alarm system is a system that give an earliest possible warning of the fire to give all personal immediately concern. Fire alarm system is important to every building for the impacts of any fire would result in the destruction of human life and asset. Fire alarm should be design at all place in the building as fixed by the National Fire Department (BOMBA) and it is consist of manual system and automatic system. Automatic system install at important places and this system can detect and give a warning of fire automatically. Smoke and heat detector are the equipment of this system and bell as the warning equipment. Normally this system is installed with automatic fire fighter system like halon gas. Manual system is the system which have to operate manually. lt is install at common places like the corridor and the staircase. Break glass is the equipment for this system and bell is the warning equipment. Other thing that is important in the fire alarm system is the FA control panel .This FA control panel is control all the FA zones at the building and it will show the right place of the fire.